Evaluasi Hasil Pengobatan Pasien Multi Drug Resistent Tuberculosis (MDR-TB) di Puskesmas Kecamatan Ciracas Jakarta Timur - Herlina Herlina; Evi Vestabilivy (Jurnal Persada Husada Indonesia, 2015)
Estimated of the number of cases of MDR TB in the world reached 489-139 in 2008. The WHO global report 2010, estimated MDR - TB patients in Indonesia amounted to 8.900 Indonesia 's ranks 8th from 27 countries with the most cases of MDR - TB . Resistance OAT cases is difficult to treat because of complex treatment, expensive, and side effects of treatment with unsatisfactory results. The research problem is to understand the results of the treatment from patients with MDR – TB. The purpose of this study is to determine the evaluation of treatment results of MDR – TB patients. The survey methods is cross sectional study design. The population is all outpatients that has been declared as MDR – TB patients. Nonparametric test analysis (Mann Whitney Test). The results showed that the outcomes of treatment evaluation of patients with Multi Drug Resistant (MDR - TB) has significant relationship variable age P - value = 0.022 ( <0.05 ) , and variable drug side effects p - value = 0.047 ( <0.05 ) , whereas from 24 respondents that has been with MDR- TB patients the result found that the greater number of respondents who failed in the treatment than the respondents were healed. Family support is a must and good environment in terms of providing support for the patient to remain on treatment and take medication regularly . The key conclusions of this research is increasing age and side effects of OAT resistance leads to successful treatment of patients.